다문화가족과 일반가족 청소년의 구강건강행태 비교 분석 - 박지혜; Ji Hye Park (Han'guk Ch'iwisaeng Hakhoe chi, 2015)
Objectives: The purpose of this study was to compare the oral health behavior in adolescents between multicultural and ordinary Korean families. Methods: The subjects were 66,797 adolescents who were derived from the web-based survey of the National 2014 Korean Youth Risk Behavior of Korean Center for Disease Control. A self-reported web-based questionnaire survey was carried out from June 1 to 30, 2013. A multicultural family is defined as the immigrant mother and child in the study. The variable included demographic, socioeconomic, and oral health related behavior. The demographic characteristics included sex, age, residence area, subjective academic achievement, type of family, education of parents, subjective economic status, and nationality before marriage. Data were analyzed by PASW statistics 18.0. Results: Tooth brushing frequency was closely related to family type, age, residence area, academic achievement, residential type, education level of the parents, and economic status. Conclusions: It is necessary to support oral health services and oral health promotion programs for the adolescents in the multicultural family.